Immunomodulatory Activity of Ethanol Extract and Kabau (Archidendron Bubalinum) Leaf Fractions on the Macrophage Phagocytosis Index in Male White Rats (Rattus Novergicus) - Aulia, Intan Sofia Irsa; Wijayanti, Tri; Saptarini, Opstaria (Jurnal Multidisiplin Madani, 2024)
Immunomodulators are substances that have the ability to balance and restore a dysfunctional immune system, reduce the body's immune response due to excessive immune activity and stimulate leukocyte cells, especially macrophages, to form a strong immune system. The aim of this study was to determine the immunomodulatory activity of kabau leaves (Archidendron bubalinum) in male white rats in terms of the phagocytosis index, number of leukocyte cell types and spleen histopathology. This research design used 35 mice as test animals and then divided them into 6 groups, namely negative control, positive control (Stimuno dose 50 mg), kabau leaf extract 20 mg, n-hexane fraction 6.66 mg, ethyl acetate fraction 4 mg, water fraction 6.66 mg, each group consisted of 5 male rats. Immunomodulatory activity was seen from the phagocytosis index and the number of leukocyte cell types at 10 and 15 minutes. The results showed that the 6 treatments had significantly different immunostimulatory activities with a significant value of less than 0.05. The results of the phagocytosis index calculation showed that the highest value was Stimuno at 3.33, then the 6.66 mg n-hexane fraction was 2.49, the 4mg ethyl acetate fraction was 1.63, the 20 mg extract was 1.26, and the water fraction was 6.66 mg. 1.27. From these results it can be concluded that kabau (Archidendron bubalinum) leaf extracts and fractions have immunostimulant activity